Master Plan for Tennessee Schools, 1995 Preparing for the 21st Century. (Distributed by ERIC Clearinghouse, 1995)
The Tennessee State Legislature passed the Education Improvement Act (EIA) in 1992, which established the Basic Education Program (BEP) as the funding formula for providing adequate, equitable, and sustainable school funding. This document presents the 1995 Master Plan for Tennessee Schools, which focuses on the priority issues that must be addressed to fulfill the promise of the EIA. The plan is consistent with the Goals 2000 legislation and addresses each of the eight national goals. The plan also addresses recommendations made by the Tennessee Business Roundtable. The plan sets the State Board of Education's priorities and defines an environment in which local school systems and the state can work for improvement. The plan focuses on nine key areas, sets goals for those areas, identifies strategies to achieve the goals, identifies new costs to implement the strategies, and notes measures of progress for each goal. In support of the plan, the board has developed an action plan outlining actions for the board and Tennessee General Assembly. A detailed work plan has also been developed. The goals, strategies, and current status of the following areas are highlighted: early childhood education, primary and middle-grades education, high school education, educational technology, professional development and teacher education, accountability/assessment, school leadership and school-based decision making, school safety, and funding. (LMI)